Death, taxes, and extra-hold hairspray - Kelly, Diane (St. Martins Paperbacks, 2012)
n agent for the IRS, Tara Holloway, while investigating a charismatic minister who is using his mega-church as a tax shelter and a crazy militant who is trying to turn Texas into a separate country, must help her boss, Lu, keep her signature strawberry blonde beehive from falling flat.